Terminal material and terminal

By using copper or copper alloy base material, Ni, Co, Fe base layer and high silver content plating in the terminal material, combined with non-conductive organic compound particles, the problems of conductive particles falling off and insufficient wear resistance caused by micro-sliding wear are solved, and efficient contact short circuit suppression and conductive performance are achieved.

CN119836494APending Publication Date: 2025-04-15KOBE STEEL LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380066420.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-22
Filing Date
2023-09-04
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing terminal materials tend to cause the fall of conductive particles under micro-sliding wear, causing short circuits to occur, and lack of wear resistance.

Method used

Terminal materials are used composed of copper or copper alloy base material, Ni, Co, Fe base layer and silver plating layer containing more than 50% silver, and non-conductive organic compound particles with an equivalent circle diameter of 50 μm or less are distributed on the silver plating layer to improve micro-sliding wear resistance and electrical conductivity.

Benefits of technology

It effectively suppresses the fall of conductive particles, avoids contact short circuit, and maintains the contact resistance below 1mΩ during the micro-sliding wear test, significantly improving wear resistance and conductive properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836494A_ABST
    Figure CN119836494A_ABST
Patent Text Reader

Abstract

The terminal material comprises, in this order: a base material formed of copper or a copper alloy; one or more bottom layers comprising one or more elements selected from the group consisting of Ni, Co, and Fe; the silver-containing film includes: a silver plating layer containing 50 mass% or more of silver; particles containing a non-conductive organic compound and having an equivalent circle diameter of 50 [mu] m or less in contact with the silver plating layer have a contact resistance of 1 m [omega] or less on the silver-containing film-side surface when subjected to the following micro-sliding wear test. A micro-sliding wear test: preparing the terminal material of a test object and a dual material which forms a hemispherical protrusion with a curvature radius R of 1.8 mm relative to the silver-containing film side surface of the terminal material, and enabling the surface of the dual material with the protrusion to be opposite to the silver-containing film side surface of the terminal material of the test object, a reciprocating slide with an applied vertical load of 3N, a slide distance of 50 [mu] m, and a slide speed of 100 [mu] m / sec is taken as one cycle, and 10000 cycles are slid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a terminal material and a terminal. Background Art

[0002] As cars become lighter in recent years, there is a demand to reduce the amount of wiring harnesses used in cars. For example, by directly connecting electronic components (called "ECUs": electronic control units) that control engines, motors, and other devices to them, it is possible to reduce the number of wiring harnesses.

[0003] Engines and motors vibrate violently, so the connectors and terminals that connect them vibrate violently. Vibration may cause micro-sliding wear of the terminals (i.e., the phenomenon of repeated small sliding and wear of the contact plating). The possibility of micro-sliding wear is further increased due to the reduction of contact pressure and the deterioration of vibration environment caused by the miniaturization of terminals in recent years.

[0004] Regarding micro-sliding wear, Patent Document 1 discloses a technique of roughening a copper alloy base material, plating it with Ni, Cu, and Sn, and performing a reflow treatment thereon to expose a predetermined Cu-Sn layer on the surface of the Sn layer. According to this technique, although micro-sliding wear is unlikely to occur, if micro-sliding wear occurs, the original material may be exposed.

[0005] In order to improve wear resistance, the application of Ag plating has also been studied. In the past, the following studies have been conducted with the purpose of improving wear resistance by increasing the hardness of Ag plating:

[0006] (1) Improve the hardness of the Ag coating by miniaturizing the grain size

[0007] (2) Hardness is increased by alloying Ag with Se (selenium) or Sb (antimony).

[0008] However, the effects of the above methods (1) and (2) on micro-sliding wear are still insufficient. In addition, Se and Sb are toxic elements, which not only require careful management, but also have the problem of reduced conductivity due to alloying.

[0009] In addition, various concepts other than increasing the hardness of the plating film have been explored to improve wear resistance, mainly as disclosed in Non-Patent Documents 1 and 2, and the following research has also been conducted:

[0010] (3) Improvement of wear resistance by eutectoid (dispersion plating) of carbon particles in the Ag plating film.

[0011] In these studies, graphite, carbon black (CB) or carbon nanotubes (CNT) that function as solid lubricants are mainly used. In fact, it is disclosed in non-patent document 1 that Ag-graphite composite plating formed by suspending graphite particles in an Ag plating solution and performing plating treatment can achieve good wear resistance, which is not only better than Ag plating, but also better than hard Ag-Sb alloy plating.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: Japanese Patent Application Laid-Open No. 2014-208904

[0015] Non-patent literature

[0016] Non-patent document 1: Materials, Vol. 58, No. 1 (2019), p41-43

[0017] Non-patent document 2: Surface Technology Association, 81st Lecture Conference Abstracts, 27A-1 Summary of the invention

[0018] Problems to be solved by the invention

[0019] In the prior art (3) disclosed in non-patent documents 1 and 2, if the carbon particles are dispersed and plated on the terminal material and sliding (plugging and unplugging) is repeated, the carbon particles retained in the plating film may fall off as the contact portion wears. Since carbon particles have good conductivity, if they fall off the terminal surface and accumulate around the contact, it may cause a short circuit of the contact. In addition, in the prior art (3), there is still a possibility that micro-sliding wear cannot be fully suppressed.

[0020] The present invention has been made in view of the above circumstances, and one of its objects is to provide a terminal material and a terminal which can sufficiently suppress contact short circuits caused by the falling of conductive particles and have sufficient micro-sliding wear resistance and conductivity.

[0021] Means of solving the problem

[0022] A first aspect of the present invention is a terminal material comprising, in order: a base material formed of copper or a copper alloy; one or more base layers formed of any one or more selected from the group consisting of Ni, Co and Fe; a silver-containing film,

[0023] The silver-containing film comprises: a silver plating layer containing 50 mass % or more of silver; particles containing a non-conductive organic compound and having an equivalent circle diameter of 50 μm or less and in contact with the silver plating layer;

[0024] The contact resistance of the surface on the silver-containing film side when the micro-sliding wear test described below was performed was 1 mΩ or less.

[0025] Micro-sliding wear test: prepare the terminal material of the test object, and a dual material having a hemispherical protrusion with a curvature radius R=1.8mm relative to the silver-containing film side surface of the terminal material, and make the surface of the dual material having the protrusion slide reciprocally relative to the silver-containing film side surface of the terminal material of the test object with an applied vertical load of 3N, a sliding distance of 50μm, and a sliding speed of 100μm / second as one cycle, and slide 10,000 cycles.

[0026] Aspect 2 of the present invention is the terminal material according to aspect 1, wherein the silver plating layer contains 90 mass % or more of silver.

[0027] A third aspect of the present invention is the terminal material according to the first or second aspect, wherein the non-conductive organic compound contains a carbonyl group (—C(═O)—) in a unit molecular structure and has no ring structure.

[0028] A fourth aspect of the present invention is a terminal using the terminal material according to any one of aspects 1 to 3.

[0029] Effects of the Invention

[0030] According to the embodiment of the present invention, a terminal material and a terminal can be provided which can sufficiently suppress contact short circuits caused by the falling of conductive particles and have sufficient micro-sliding wear resistance and conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a schematic cross-sectional view of an example of a terminal material according to an embodiment of the present invention.

[0033] Figure 2 It is a schematic cross-sectional view of another example of the terminal material according to the embodiment of the present invention.

[0034] Figure 3 It is a schematic cross-sectional view of another example of the terminal material according to the embodiment of the present invention.

[0035] Figure 4 This is the evaluation result of the micro-sliding wear resistance of the No. 1 terminal material.

[0036] Figure 5 These are the results of evaluating the micro-sliding wear resistance of the No. 2 terminal material.

[0037] Figure 6 These are the results of evaluating the micro-sliding wear resistance of the No. 3 terminal material.

[0038] Figure 7 These are the results of evaluating the micro-sliding wear resistance of the No. 4 terminal material.

[0039] Figure 8 These are the results of evaluating the micro-sliding wear resistance of the No. 5 terminal material.

[0040] Fig. 9 These are the results of evaluating the micro-sliding wear resistance of the No. 6 terminal material. DETAILED DESCRIPTION

[0041] The inventors of the present invention have studied from various angles to realize a terminal material that can fully suppress contact short circuits caused by the shedding of conductive particles and has sufficient micro-sliding wear resistance and conductivity. As a result, it was found that by achieving a prescribed layer structure of a silver-containing film containing particles of a non-conductive organic compound with an equivalent circle diameter of 50 μm or less that is in contact with the silver-plated layer (carried on the silver-plated layer), sufficient micro-sliding wear resistance and conductivity can be obtained. This is believed to be due to the fact that micro-sliding (and the resulting heat release, etc.) causes, for example, a portion of the non-conductive organic compound to decompose and diffuse and move to the vicinity of the terminal material surface, and / or a portion of the non-conductive organic compound reacts with the silver-plated layer near the terminal material surface, reducing the friction coefficient near the terminal material surface, etc., thereby causing an increase in micro-sliding wear resistance. In addition, the decomposition products and reactants are small in amount, and it is believed that the conductivity of the terminal material will not be reduced. Furthermore, since the non-conductive organic compound is in contact with the silver plating layer in the form of particles rather than a film, the silver plating layer can be exposed on the surface of the terminal material, and thus the initial conductivity as the terminal material can be maintained.

[0042] As described above, it is possible to realize a terminal material that can sufficiently suppress the risk of contact short circuit due to the falling of conductive particles and has sufficient micro-wear resistance and conductivity.

[0043] In addition, the above-mentioned mechanism does not limit the technical scope of the embodiment of the present invention.

[0044] The following describes in detail each requirement specified in the embodiment of the present invention.

[0045] The terminal material of an embodiment of the present invention comprises, in order: a base material formed of copper or a copper alloy; one or more base layers composed of any one or more selected from the group consisting of Ni, Co and Fe; a silver-containing film, the silver-containing film comprising: a silver plating layer containing more than 50 mass % of silver; particles containing a non-conductive organic compound having an equivalent circle diameter of less than 50 μm in contact with the silver plating layer, and the contact resistance of the side surface of the silver-containing film when the following micro-sliding wear test is performed is less than 1 mΩ.

[0046] Micro-sliding wear test: prepare the terminal material of the test object, and a dual material having a hemispherical protrusion with a curvature radius R=1.8mm relative to the silver-containing film side surface of the terminal material, and make the surface of the dual material having the protrusion slide reciprocally relative to the silver-containing film side surface of the terminal material of the test object with an applied vertical load of 3N, a sliding distance of 50μm, and a sliding speed of 100μm / second as one cycle, and slide 10,000 cycles.

[0047] According to the above, short circuit of the contact point due to the falling of the conductive particles can be sufficiently suppressed, and sufficient micro-sliding wear resistance and conductivity can be exhibited.

[0048] Figure 1 A schematic cross-sectional view showing an example of a terminal material according to an embodiment of the present invention. Figure 1 In the embodiment, the terminal material 1 includes: a base material 2 formed of copper or a copper alloy (hereinafter referred to as "base material 2"); a base layer 3 composed of one or more layers selected from the group consisting of Ni, Co and Fe; a silver-containing film 4, wherein the silver-containing film 4 includes a silver plating layer 4a and particles 4b containing a non-conductive organic compound having an equivalent circle diameter of 50 μm or less and contacting (adhering to) the silver plating layer 4a (hereinafter referred to as "particles 4b"). The contact resistance of the side surface of the silver-containing film 4 of the terminal material 1 when the above-mentioned micro-sliding wear test is implemented is less than 1 mΩ.

[0049] The material of the base material 2 may be pure copper such as oxygen-free copper (OFC), or one or more copper alloys such as CuFeP, CuNiSi, CuTiCr, CuSnP, and CuMg. In addition, the required properties (conductivity, elasticity, strength, etc.) of the terminal material vary depending on the place of use. Therefore, the material of the base material 2 (and its tempering conditions) may be appropriately selected according to the required properties.

[0050] The terminal material 1 (and the terminal using the same) containing the base material 2 can be used in a high temperature environment such as the engine room of an internal combustion engine or the connection part of a battery of an electric vehicle. In a high temperature environment, Cu of the base material 2 diffuses to the silver-containing film 4 and reaches the surface of the silver-containing film 4, further generating Cu oxide, which may increase the contact resistance of the terminal material 1.

[0051] Therefore, one or more layers of the underlayer 3 made of one or more selected from the group consisting of Ni, Co, and Fe are provided between the base material 2 and the silver-containing film 4. This can suppress the diffusion of Cu from the base material 2 into the silver-containing film 4.

[0052] In view of plating workability, etc., the base layer 3 particularly preferably contains Ni. In addition, the base layer 3 may be a multi-layered one.

[0053] The average thickness of the bottom layer 3 (for example, the average thickness of the bottom layer 3 obtained from any two or more cross sections of the terminal material) is preferably 0.1 μm or more, and more preferably 0.2 μm or more. This can effectively prevent the diffusion of copper by suppressing pores and the like. On the other hand, if the bottom layer 3 becomes thicker, the diffusion suppression effect of Cu may be saturated. From the viewpoint of productivity, cost, and processability during terminal forming, the average thickness of the bottom layer 3 is preferably 3.0 μm or less, and more preferably 2.0 μm or less.

[0054] The silver plating layer 4a is a layer containing 50% by mass or more of silver. As the silver plating layer 4a, in addition to the soft Ag plating, hard Ag plating, glossy Ag plating, and semi-glossy Ag plating used for the usual terminal surface treatment, an Ag alloy plating layer containing Sn and / or Ni etc. may also be used for the purpose of improving the corrosion resistance (sulfurization resistance etc.) and micro-sliding wear resistance of the silver-containing film 4. However, since micro-sliding wear resistance can be mainly provided by the particles 4b containing non-conductive organic compounds, when there is no other purpose such as improving corrosion resistance, it is preferred to use a pure Ag plating layer with excellent conductivity as a carrier, for example, preferably containing 90% by mass or more of silver, more preferably containing 95% by mass or more, and further preferably containing 99% by mass or more.

[0055] The average thickness of the silver plating layer 4a (for example, the average thickness of the silver plating layer 4a obtained from any two or more cross sections of the terminal material) is not particularly limited and can be appropriately adjusted according to the application, for example, 100 μm or less, and can also be 50 μm or less.

[0056] The particles 4b containing a non-conductive organic compound are "non-conductive" and do not exhibit conductivity, and for example, the volume resistivity measured according to ASTM D257 is about 10 3 [Ω·cm] or more.

[0057] Regarding the particles 4b containing non-conductive organic compounds, the so-called "organic compounds" refer to compounds containing carbon, excluding compounds with simple structures such as carbon monoxide, carbon dioxide, carbonates, cyanic acid, cyanates, thiocyanates, B4C and SiC. For example, silicone resins having siloxane bonds (-Si-O-Si-) as the main chain and organic groups in the side chains are included in the "organic compounds" in this specification.

[0058] The non-conductive organic compound preferably contains a fluorine group (-F), a methyl group (-CH3), a carbonyl group (-C(=O)-), an amino group (-NR 1 R 2 In, R 1 and R 2 is hydrogen or a hydrocarbon group, R1 and R 2 Any one or more selected from the group consisting of a carbonyl group (-C(=O)-) and a hydroxyl group (-OH). More preferably, the unit molecular structure contains a carbonyl group (-C(=O)-) and has no ring structure. This can further improve the micro-sliding wear resistance.

[0059] Here, the “unit molecular structure” means one repeating unit in the case of a macromolecular (polymer) and means a single molecule in the case of a non-polymer.

[0060] Regarding the particles 4b containing non-conductive organic compounds, the so-called "particles" means relatively small substances with an equivalent circle diameter of 50 μm or less, and the shape can be any shape. In one embodiment of the present invention, from the viewpoint of conductivity, the average particle size (average equivalent circle diameter) of the particles 4b can be 10 μm or less. In addition, in one embodiment of the present invention, from the viewpoint of micro-sliding wear resistance, the average particle size of the particles 4b can be 0.1 μm or more.

[0061] Figure 2 A schematic cross-sectional view of another example of a terminal material according to an embodiment of the present invention is shown, in which particles 4b are buried in the silver plating layer 4a in the terminal material 11. Here, "buried" means that each particle 4b is completely buried in the silver plating layer 4a, or a part of it is buried in the silver plating layer 4a, and the rest is exposed on the surface of the silver plating layer 4a.

[0062] Figure 3 A schematic cross-sectional view showing another example of the terminal material according to the embodiment of the present invention shows that in the terminal material 21 , the particles 4 b are completely buried in the silver plating layer 4 a . Figure 3 In this case, the particles 4b may be of a size that can be completely buried in the silver plating layer 4a, that is, the average particle size of the particles 4b may be lower than the thickness of the silver plating layer 4a.

[0063] In the terminal material of the embodiment of the present invention, the so-called "particle contact" is, for example, Figure 1 In this way, the particles 4b can contact (attach) to the surface of the silver-plated layer 4a, for example, the particles 4b can also be coprecipitated (buried) in the silver-plated layer 4a. In this case, each particle 4b can be as Figure 3 This is completely buried in the silver plating 4a, and can also be as Figure 2 In this way, a part of each particle 4b is exposed on the surface of the silver plating layer 4a. Whether the particles are in "contact" can be determined by observing the cross section of the terminal material 1 (11, 21), for example.

[0064] From the viewpoint of further improving the conductivity (further reducing the contact resistance), it is preferred that Figure 2Thus, the particles 4b are coprecipitated (buried) in the silver plating layer 4a, or as Figure 3 Thus, the particle 4b is completely buried in the silver plating layer 4a. On the other hand, from the viewpoint of further improving the micro-sliding wear resistance, it is preferred as follows Figure 1 Thus, the particle 4b is in contact (attached) with the surface of the silver-plated layer 4a, or as Figure 2 Thus, the particles 4b are co-precipitated (buried) in the silver plating layer 4a.

[0065] The terminal materials 1, 11 and 21 of the embodiment of the present invention may, depending on the circumstances, have conductive particles in contact with the silver plating 4a, but the fewer conductive particles there are, the more they can suppress contact short circuits caused by their shedding, which is preferred. Therefore, it is preferred that more than 50% by volume of the particles in contact with the terminal materials 1, 11 and 21 of the embodiment of the present invention are particles 4b containing non-conductive organic compounds, more preferably more than 60% by volume, more than 70% by volume, more than 80% by volume, more than 90% by volume, and further preferably all (100% by volume) are particles 4b containing non-conductive organic compounds. In addition, the terminal materials 1, 11 and 21 of the embodiment of the present invention may also contact inorganic particles depending on the circumstances.

[0066] The terminal materials 1 , 11 , and 21 according to the embodiment of the present invention may include other layers (eg, strike plating, etc.) after achieving the purpose of the present invention.

[0067] As a method for manufacturing a terminal material 1 according to an embodiment of the present invention, for example, first, a base material 2 such as a copper plate is electrified under normal conditions to form a base layer 3 through a predetermined plating solution containing a material having a copper diffusion inhibiting effect (one or more selected from the group consisting of Ni, Co and Fe). Thereafter, a silver (or silver alloy) plating solution is electrified under normal conditions to form a silver plating layer 4a. Then, a dispersion containing particles 4b of a non-conductive organic compound is applied to the surface. Thus, a terminal material 1 can be obtained. In addition, depending on the circumstances, a base silver plating treatment may be performed before the silver plating treatment.

[0068] In the above-mentioned manufacturing method, particles 4b containing non-conductive organic compounds are dispersed in a silver (or silver alloy) plating solution and electroplating is performed while stirring, thereby obtaining a terminal material in which particles 4b containing non-conductive organic compounds are co-precipitated in the silver plating layer 4a (terminal material 11 in which a portion of the particles 4b is exposed on the surface of the silver plating layer 4a or terminal material 21 in which the particles 4b are completely buried in the silver plating layer 4a).

[0069] In the process of dispersing the particles 4b in the plating solution and performing electroplating to coprecipitate the particles 4b in the silver plating layer 4a, the following reactions (A) and (B) proceed simultaneously.

[0070] (A) On the surface of the substrate, there is a reaction of electrostatic or physical adsorption (contact) of particles dispersed in the liquid

[0071] (B) The reaction of the silver plating layer 4a accumulating (growing) on ​​the substrate surface

[0072] The particles 4b adsorbed in (A) are incorporated into the silver-plated layer 4a of (B) to form "eutectoid". Under the condition that the eutectoid plating is carried out stably, the particles 4b adsorbed at the beginning of the reaction are incorporated into the silver-plated layer 4a, and at the same time, new particles 4b are adsorbed. Therefore, even when the plating process is stopped, the exposure of the particles 4b from the outermost surface can still be seen in most cases. In the usual eutectoid plating process, it is easy to manufacture the terminal material 11 with a part of the particles 4b exposed on the surface of the silver-plated layer 4a.

[0073] Here, the amount of the particles 4b co-precipitated in the silver-plated layer 4a is determined by the balance between the adsorption frequency (A) and the plating film growth rate (B), so the co-precipitation amount can be changed by changing the plating conditions (and the plating bath conditions). For example, in the final stage of the plating treatment, a plating solution that does not contain the particles 4b dispersed in the plating solution is used for treatment, or the adsorption frequency (A) is reduced by changing the stirring speed of the plating solution, etc., so that a layer that does not co-precipitate the particles 4b can be provided on the outermost surface side of the plating, thereby manufacturing the terminal material 21 in which the particles 4b are completely buried in the silver-plated layer 4a.

[0074] The terminal materials 1, 11 and 21 of the embodiments of the present invention not only have sufficient conductivity, but also have sufficient resistance to micro-sliding wear. Specifically, the terminal materials 1, 11 and 21 of the embodiments of the present invention can have an initial contact resistance of less than 1.0 mΩ, and the following micro-sliding wear test can still keep the contact resistance below 1.0 mΩ after 10,000 cycles. It is preferred that the terminal materials 1, 11 and 21 of the embodiments of the present invention can still keep the contact resistance below 1.0 mΩ even after 20,000 cycles of the following micro-sliding wear test.

[0075] <Micro-sliding wear test>

[0076] Prepare a terminal material of the test object and a mating material on which a hemispherical protrusion with a curvature radius R=1.8 mm is formed, for example, by a manual press, relative to the silver-containing film side surface of the terminal material, and make the surface of the mating material with the protrusion relative to the silver-containing film side surface of the terminal material of the test object slide back and forth at an applied vertical load of 3N, a sliding distance of 50μm, and a sliding speed of 100μm / second as one cycle, and perform a predetermined cyclic sliding. As a sliding test machine, for example, CRS-B1050CHO manufactured by Yamazaki Seiki Laboratories can be used.

[0077] The terminal of the embodiment of the present invention includes the terminal materials 1, 11 and 21 of the embodiment of the present invention. The terminal of the embodiment of the present invention can be manufactured by forming the terminal materials 1, 11 and 21 of the embodiment of the present invention into a terminal shape, or first forming the base material 2 into a terminal shape, and then forming a base layer 3 composed of one or more layers selected from the group consisting of Ni, Co and Fe and a silver-containing film 4 (silver plating 4a and particles 4b containing non-conductive organic compounds) on the base material 2. The terminal of the embodiment of the present invention can be used to directly connect equipment such as engines and motors to ECUs.

[0078] Example

[0079] The embodiments of the present invention are not limited to the following embodiments, and may be appropriately modified within the scope of the above and below-mentioned purposes, and all of these are included in the technical scope of the embodiments of the present invention.

[0080] A pure copper sheet with a thickness of 0.3 mm (copper content of 99 mass % or more) was used as the base material. After the base material surface was degreased by acetone cleaning, a matte Ni Watt bath was used with a Ni plate as the counter electrode at 5 A / dm 2 The current density was 5A / dm for 2 minutes to form a 1μm thick base layer (Ni content 99% or more). Then, a commercially available base Ag plating solution (Dain Silver GPE-ST manufactured by Yamato Chemical Co., Ltd.) was used to plate the base layer at 5A / dm 2 The current density was 10000 for 1 minute to form a base Ag plating layer with a thickness of about 0.1 μm (silver content 99 mass % or more). Then, a commercially available non-cyanide semi-gloss Ag plating solution (Dain Silver GPE-SB manufactured by Yamato Chemical Co., Ltd.) was used to disperse various particles containing non-conductive organic compounds with an equivalent circle diameter of 50 μm or less and a surfactant (dispersant) in the plating solution in a specified amount, and the solution was stirred at 3 A / dm with a pure Ag plate as the counter electrode. 2 The current density was 0.040 for 5 minutes, and the terminal materials No. 1 to 4 were obtained, which contained a silver-containing film in which each particle was coprecipitated (buried) in a semi-glossy Ag plating layer (silver content 99 mass % or more) with a thickness of about 10 μm. In addition, SURFLON S231 (manufactured by AGC SEIMI CHEMICAL) was used as a surfactant in No. 1 to 3, and the addition amount was 50 g / L. In addition, in No. 4, sodium naphthalenesulfonate was used as a surfactant, and carboxymethyl cellulose (CMC) was used as a dispersant (stabilizer).

[0081] As a comparison with the terminal materials No. 1 to 4, terminal materials No. 5 and 6 were prepared without particles containing non-conductive organic compounds. No. 5 is different from No. 1 to 4 in that various particles containing non-conductive organic compounds and surfactants (dispersants) are not dispersed in the semi-gloss Ag plating solution, and a semi-gloss Ag plating layer with a thickness of about 10 μm (silver content of more than 99 mass %) is formed. No. 6 is different from No. 1 to 4 in that the primer Ag plating solution is a cyanide bath, and after a primer Ag plating layer with a thickness of about 0.1 μm (silver content of more than 99 mass %) is formed, the semi-gloss Ag plating solution is changed to a glossy Ag plating solution (N-BRIGHT manufactured by Metalor Technologies), and various particles containing non-conductive organic compounds and surfactants (dispersants) are not dispersed in the glossy Ag plating solution. A pure Ag plate is used as the counter electrode, and the reaction is carried out at 1.5 A / dm 2 The current was passed for 15 minutes at a current density of , to form a glossy Ag plating layer (silver content 99 mass % or more) with a thickness of about 10 μm.

[0082]

Table 1

[0083]

[0084] For the terminal materials No. 1 to No. 6, initial contact resistance evaluation and micro-sliding wear resistance evaluation were performed.

[0085] <Initial contact resistance evaluation>

[0086] For the silver film side surface of the terminal materials No. 1 to 6, an electric contact simulator (manufactured by Yamazaki Seiki Laboratories) was used to perform five measurements by the four-terminal method under the conditions of an open circuit voltage of 20 mV, a current of 10 mA, and a load of 3 N, and the average value was taken as the initial contact resistance value. Contact resistances higher than 1.0 mΩ were considered poor in conductivity (×), and those below 1.0 mΩ were considered sufficient in conductivity (○).

[0087] <Evaluation of micro-sliding wear resistance>

[0088] Prepare terminal materials No. 1 to 6 (size 10cm×10cm), and a dual material (size 0.5cm×5cm) with a hemispherical protrusion with a radius of curvature R=1.8mm formed by a manual press on the silver-containing film side surface of the terminal materials No. 1 to 6. Make the surface of the dual material with the protrusion relative to the silver-containing film side surface of the terminal materials No. 1 to 6. Use CRS-B1050CHO manufactured by Yamazaki Seiki Laboratories as a sliding tester, and perform reciprocating sliding with an applied vertical load of 3N, a sliding distance of 50μm, and a sliding speed of 100μm / second as one cycle. Perform specified cyclic sliding, and measure the contact resistance after each cycle in the same way as above. The results are shown in Figures 4 to 9 middle. Figures 4 to 9 These are the results of micro-sliding wear tests performed on the terminal materials of Test Nos. 1 to 6 with N=2.

[0089] In the case of a short cycle number in the contact resistance of more than 1.0 mΩ, N = 2, less than 10,000 is considered bad (×), more than 10,000 and less than 20,000 is considered 0 (sufficient), and more than 20,000 is considered ◎ (good). In addition, after 20,000 cycles, the wear marks were observed to evaluate whether the base material (or base layer) was exposed.

[0090] The above results are summarized in Table 2. In addition, in the "Preventing short circuits" column, when more than 50% by volume of the particles in contact with the silver plating layer are non-conductive particles, the short circuit of the contact caused by the falling of particles can be fully suppressed (○), and when less than 50% by volume of the particles in contact with the silver plating layer are non-conductive particles (that is, when more than 50% by volume of the particles in contact with the silver plating layer are conductive particles), the short circuit of the contact may be caused by the falling of particles (×). In the "Comprehensive judgment" column, when all the columns of "Preventing short circuits", "Conductivity" and "Resistance to micro-sliding wear" are judged as "○", it is expressed as "○", and on this basis, when the column of "Resistance to micro-sliding wear" is judged as "◎", it is expressed as "◎", and when one of the columns of "Preventing short circuits", "Conductivity" and "Resistance to micro-sliding wear electronic components" is judged as "×", it is expressed as "×".

[0091]

Table 2

[0092]

[0093] The results in Table 2 allow for the following investigations. The terminal materials No. 1 to 4 in Table 2 all meet the requirements specified in the embodiments of the present invention, can fully suppress short circuits at contacts caused by the shedding of conductive particles, and have sufficient conductivity and micro-sliding wear resistance. Among them, the silver-containing films No. 1 to 3 meet the preferred requirements that the non-conductive organic compound contains a carbonyl group (-C(=O)-) in the unit molecular structure and has no ring structure, so the number of cycles at which the contact resistance is higher than 1.0 mΩ is more than 20,000.

[0094] The contact resistance of the terminal materials No. 5 and 6 became higher than 1.0 mΩ when the micro-sliding wear test was less than 10,000 cycles. This is believed to be because the particles containing non-conductive organic compounds in the terminal materials No. 5 and 6 did not contact the silver plating layer, and the micro-sliding wear easily led to the exposure of the base material (or base layer), and the oxidation of the base material increased the contact resistance. In addition, compared with No. 5, No. 6 hardened the silver plating layer with the help of the brightener, and although the time of contact resistance increase was delayed, no significant improvement was confirmed.

[0095] The present application claims priority based on Japanese Patent Application No. 2022-151505, filed on September 22, 2022. The entire disclosure of Japanese Patent Application No. 2022-151505 is incorporated herein by reference.

[0096] Description of Reference Numerals

[0097] 1Terminal Material

[0098] 2. Base material

[0099] 3 Bottom layer

[0100] 4Silver-containing film

[0101] 4a Silver plating

[0102] 4b Particles containing non-conductive organic compounds

[0103] 11Terminal Material

[0104] 21Terminal material

Claims

1. A terminal material comprising, in order: a base material formed of copper or a copper alloy; one or more base layers formed of any one or more selected from the group consisting of Ni, Co and Fe; a silver-containing film, The silver-containing film comprises: a silver plating layer containing 50 mass % or more of silver; particles containing a non-conductive organic compound and having an equivalent circle diameter of 50 μm or less and in contact with the silver plating layer; The contact resistance of the silver-containing film side surface during the micro-sliding wear test described below was 1 mΩ or less. Micro-sliding wear test: prepare the terminal material of the test object, and a dual material having a hemispherical protrusion with a curvature radius R=1.8mm relative to the silver-containing film side surface of the terminal material, and make the surface of the dual material having the protrusion slide reciprocally relative to the silver-containing film side surface of the terminal material of the test object with an applied vertical load of 3N, a sliding distance of 50μm, and a sliding speed of 100μm / second as one cycle, and slide 10,000 cycles.

2. The terminal material according to claim 1, wherein The silver plating layer contains 90 mass % or more of silver.

3. The terminal material according to claim 1, wherein The non-conductive organic compound contains a carbonyl group (-C(=O)-) in a unit molecular structure and has no ring structure.

4. The terminal material according to claim 2, wherein The non-conductive organic compound contains a carbonyl group (-C(=O)-) in a unit molecular structure and has no ring structure. 5 . A terminal using the terminal material according to claim 1 .

Citation Information

Patent Citations

  • Electroconductive material superior in resistance to fretting corrosion for connection component

    JP2014208904A

  • Application system, terminal, my-number card application method, and program

    JP2022151505A